Systemically Injected Exosomes Targeted to EGFR Deliver Antitumor MicroRNA to Breast Cancer Cells - Ohno, Shin-ichiro; Takanashi, Masakatsu; Sudo, Katsuko; Ueda, Shinobu; Ishikawa, Akio; Matsuyama, Nagahisa; Fujita, Koji; Mizutani, Takayuki; Ohgi, Tadaaki; Ochiya, Takahiro; Gotoh, Noriko; Kuroda, Masahiko (Molecular therapy, 2013)
Despite the therapeutic potential of nucleic acid drugs, their clinical application has been limited in part by a lack of appropriate delivery systems. Exosomes or microvesicles are small endosomally derived vesicles that are secreted by a variety of cell types and tissues. Here, we show that exosomes can efficiently deliver microRNA (miRNA) to epidermal growth factor receptor (EGFR)-expressing breast cancer cells. Targeting was achieved by engineering the donor cells to express the transmembrane domain of platelet-derived growth factor receptor fused to the GE11 peptide. Intravenously injected exosomes delivered let-7a miRNA to EGFR-expressing xenograft breast cancer tissue in RAG2–/– mice. Our results suggest that exosomes can be used therapeutically to target EGFR-expressing cancerous tissues with nucleic acid drugs.